2018
DOI: 10.1182/blood-2018-99-112697
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Follow up of the Phase 3 Pollux Study of Daratumumab Plus Lenalidomide and Dexamethasone (D-Rd) Versus Lenalidomide and Dexamethasone (Rd) Alone in Relapsed or Refractory Multiple Myeloma (RRMM)

Abstract: Introduction: Daratumumab is a human, CD38-targeted, IgGκ monoclonal antibody with both direct on-tumor and immunomodulatory mechanisms of action. In the phase 3 POLLUX study, D-Rd reduced the risk of disease progression or death by 63% and significantly increased the overall response rate (ORR) versus Rd alone (93% vs 76%; P <0.001) in RRMM patients (pts). When combined with standard of care regimens across three phase 3 studies including POLLUX, daratumumab demonstrated ≥50% reductions in the risk of prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
(42 reference statements)
1
16
0
Order By: Relevance
“…Among patients with keratopathy worse than baseline at the end of treatment, the events resolved in 9 (36%) of 25 patients in the 2.5 mg/kg cohort, with a median time to resolution of 71 days (interquartile range (IQR) 57-99), and 8 (28%) of 29 patients in the 3.4 mg/kg cohort, with a median time to resolution of 96 days . No benefit was observed for prophylactic steroid eyedrop administration, as median time to keratopathy was similar between eyes treated prophylactically with corticosteroid eye drops and without (24 (IQR 21-30) and 27 days, respectively in the 2.5 mg/kg cohort and 25 (9-40) and 25 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) days, respectively in the 3.4 mg/kg cohort). 203 Panel recommendations ► Prior to receiving belantamab mafodotin the patient should receive a complete ophthalmological examination.…”
Section: Administration Dosing and Monitoringmentioning
confidence: 95%
See 2 more Smart Citations
“…Among patients with keratopathy worse than baseline at the end of treatment, the events resolved in 9 (36%) of 25 patients in the 2.5 mg/kg cohort, with a median time to resolution of 71 days (interquartile range (IQR) 57-99), and 8 (28%) of 29 patients in the 3.4 mg/kg cohort, with a median time to resolution of 96 days . No benefit was observed for prophylactic steroid eyedrop administration, as median time to keratopathy was similar between eyes treated prophylactically with corticosteroid eye drops and without (24 (IQR 21-30) and 27 days, respectively in the 2.5 mg/kg cohort and 25 (9-40) and 25 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) days, respectively in the 3.4 mg/kg cohort). 203 Panel recommendations ► Prior to receiving belantamab mafodotin the patient should receive a complete ophthalmological examination.…”
Section: Administration Dosing and Monitoringmentioning
confidence: 95%
“…Furthermore, when combined with standard-of-care regimens across multiple phase III studies including POLLUX and CASTOR (borte-zomib+dexamethasone±dara), the addition of dara led to ≥50% reductions in the risk of progression or death, doubled complete response (CR) rates and tripled MRDnegative rates at the 10 -5 sensitivity threshold in patients with RRMM. [28][29][30] A 4-year follow-up analysis of POLLUX examined 569 randomized patients (D-Rd, n=286; Rd, n=283). At a median follow-up of 51.3 months, D-Rd significantly prolonged progression-free survival (PFS) versus Rd (median 45.8 vs 17.5 months; HR 0.43; 95% CI 0.35 to 0.54; p<0.0001).…”
Section: Daratumumabmentioning
confidence: 99%
See 1 more Smart Citation
“…Updated data on the phase 3 CASTOR and POLLUX trials demonstrated a sustained significant PFS and OS benefit in relapsed and refractory multiple myeloma (RR-MM) patients treated with daratumumab containing triplets [13,14]. Also, a joint analysis from the CASTOR, POLLUX, and MMY1001 trials showed that both the combination of daratumumab with pomalidomide as wells as with carfilzomib showed similar response rates in lenalidomide-refractory patients when compared to non-refractory patients [15].…”
Section: Relapsed and Refractory Multiple Myelomamentioning
confidence: 99%
“…In this setting, continuous treatment has traditionally aimed at disease control over time, with a favorable toxicity profile, and this remains true for heavily pretreated patients. In early relapses, however, the administration of newer combination regimens with novel agents-including the second-generation proteasome inhibitor (PI) carfilzomib or the anti-CD38 monoclonal antibody (mAb) daratumumab-allowed the achievement of deep responses, with complete response (CR) rates ranging from 20% to 43% [9][10][11][12][13][14]. Remarkably, with daratumumab-based combinations, the MRD-negative status was achieved in 12-26% of relapsed patients [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%